The Implementation Of Character Values Through Islamic Religious Education (PAI) Lessons In Online Learning At SDIT Al-Fatih Baturaja - Inti Pitasari; Dian Erlina; Elhefni Elhefni; Abdullah Idi; Leny Marlina (Journal of Research in Islamic Education, 2021)
This study aims to find out: 1) what obstacles are faced by teachers in instilling character values ​​through Islamic Religious Education subjects in online learning at SDIT Al-Fatih Baturaja. 2) To find out the strategies used by PAI teachers to instill character values ​​in online learning. This type of research is descriptive qualitative, with data collection observations, interviews and documentation. This qualitative approach is based on the research objective which is to find a solution to problems in instilling character values ​​through PAI subjects in online learning at SDIT Al-Fatih Baturaja. The results of this study indicate that: 1) Cultivating character values ​​through PAI subjects In online learning it is very important to be implanted and developed in every PAI subject, because the character possessed by students is very important to be applied in life in society. 2) obstacles to inculcating character values ​​through PAI subjects in online learning in the form of level of awareness, lack of support from both parents, decreased discipline, not being able to monitor directly, internet quotas, and the environment. The solution in overcoming the obstacles to inculcating character values ​​through PAI subjects in online learning at SDIT Al-Fatih Baturaja is to give more attention to students, invite parents to participate in educating character and be active in students' daily activities, provide deeper understanding of the positive and negative impacts of increasingly advanced technology, providing focus for students' learning time at home, providing motivation and support to students, and facilitating students in financial terms.